Can eating nuts reduce the risk of dementia? - narrative review - Malaka, Ewa; Byrska, Martyna; Zubiak, Marlena; Barska-Kobylińska , Hanna; Janura, Marta; Langner, Sara (Quality in Sport, 2025)
Introduction: Dementia is a growing health problem in aging societies, and its prevention is one of the most important challenges of modern medicine. In recent years, there has been growing interest in the role of diet in reducing the risk of developing dementia, including the consumption of nuts, which are a rich source of nutrients with potential neuroprotective properties. Aim of the Study: The aim of this study is to review the available research on the effect of nut intake on the risk of developing dementia and to analyze the biological mechanisms that may explain this association. Materials and Methods: A review of available studies on the association between nut consumption and dementia risk was conducted. Data were collected from a variety of cohort and clinical studies that included people of different ages, most often the elderly, and monitored their diet and cognitive function. The analyses included different types of nuts, such as walnuts, almonds, and Brazil nuts. Results: Available research suggests that regular consumption of nuts may benefit cognitive function and reduce the risk of dementia. Mechanisms of potential action include antioxidant properties, anti-inflammatory properties and what may indirectly protect the brain from degeneration. Despite promising results, not all studies show unequivocal benefits, which may be due to differences in study populations, methodology and the type of nuts consumed. Conclusion: Nut consumption may be one component of dementia prevention, but further research is needed to better understand the mechanisms of action and to determine the optimal amounts and types of nuts.